2018
DOI: 10.4081/hr.2018.7658
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplasia-related acute myeloid leukemia and acute promyelocytic leukemia: concomitant occurrence of two molecularly distinct diseases

Abstract: Concurrent presentation of acute promyelocytic leukemia (APL) with other hematologic diseases in the absence of previous chemotherapy or ionizing radiotherapy treatment is very rare. We present a case of simultaneous occurrence of APL with myelodysplastic syndrome (MDS)-related acute myeloid leukemia (AML). A 43-yearold female presented with 3 month of history fatigue, night sweats, chills and pancytopenia. Bone marrow aspirate and biopsy demonstrated 20% myeloid blasts with dysplastic changes admixed with abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Considerable research has implicated DNR as an anti-cancer drug [1,3,4,5,6,7]. Previously, we reported that DNR delayed lymphoma cell growth and high levels of CHO induced DNR-resistance [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has implicated DNR as an anti-cancer drug [1,3,4,5,6,7]. Previously, we reported that DNR delayed lymphoma cell growth and high levels of CHO induced DNR-resistance [2].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, liposomal cytarabine-daunorubicin CPX-351 has been approved as a new drug for treating acute myeloid leukemia [5]. The use of DNR combined with cytarabine and trans retinoic acid was able to induce complete remission of concomitant myelodysplasia-related acute myeloid leukemia and acute promyelocytic leukemia in a 43-year old patient [6]. A promising cancer therapy has been developed endocapsuling DNR in injectable polymeric nanocontainers [7].…”
Section: Introductionmentioning
confidence: 99%